Biomass Yield, Nitrogen Accumulation and Nutritive Value of Mavuno Grass Inoculated with Plant Growth-promoting Bacteria - Sá, G. C.R. [UNESP]; Carvalho, C. L.M. [UNESP]; Moreira, A.; Hungria, M.; Nogueira, M. A.; Heinrichs, R. [UNESP]; Soares Filho, C. V. [UNESP] (Taylor & Francis, 2019)
The objective of this study was to evaluate the effects of strains of Azospirillum brasilense, Pseudomonas fluorescens and Rhizobium tropici on the shoot dry weight (SDW) and root dry weight (RDW) yield, N uptake and nutritive value of ‘Mavuno’ grass inoculated with plant growth-promoting bacteria. We evaluated the effects of inoculation with the Ab-V5 and Ab-V6 strains of Azospirillum brasilense and Pseudomonas fluorescens or co-inoculation with Rhizobium tropici and Ab-V6, with and without nitrogen (N) application, as well as re-inoculations. The growth promoting bacteria + N promoted increases in SDW and RDW yield, tillers dry weight, relative chlorophyll index and N uptake. There were no effects of re-inoculation by Azospirillum brasilense, Pseudomonas fluorescens and Rhizobium tropici on nutrition, nutritive value and SDW and RDW yield, demonstrating that this technique still needs further studies with ‘Mavuno’ grass in the form and the correct period to be performed.
Keywords: Azospirillum brasilense; biological nitrogen fixation; Pseudomonas fluorescens; Rhizobium tropici; Urochloa spp